2018
DOI: 10.1111/sjop.12466
|View full text |Cite
|
Sign up to set email alerts
|

The effect of language, spatial factors, masker type and memory span on speech‐in‐noise thresholds in sequential bilingual children

Abstract: This study considers whether bilingual children listening in a second language are among those on which higher processing and cognitive demands are placed when noise is present. Forty-four Swedish sequential bilingual 15 year-olds were given memory span and vocabulary assessments in their first and second language (Swedish and English). First and second language speech reception thresholds (SRTs) at 50% intelligibility for numbers and colors presented in noise were obtained using an adaptive procedure. The tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Memory span was not a significant predictor of SiN perception when language ability and speech perception in quiet were taken into account. The finding of a significant association between memory span and SiN is in line with a number of previous studies of children (MacCutcheon et al, 2018, 2019, submitted). Still, our results suggest that for children with hearing loss and language disorder, general language ability may be more closely related to SiN perception.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Memory span was not a significant predictor of SiN perception when language ability and speech perception in quiet were taken into account. The finding of a significant association between memory span and SiN is in line with a number of previous studies of children (MacCutcheon et al, 2018, 2019, submitted). Still, our results suggest that for children with hearing loss and language disorder, general language ability may be more closely related to SiN perception.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the sentences mostly describe well known scenarios and thus allow the participant to use linguistic context and world knowledge to compensate for memory limitations. By contrast, the SiN task used by MacCutcheon et al (2018; 2019, submitted) where all sentences follow the same template with some items (colors and numbers) replaced in each sentence, does not allow for use of linguistic context or world knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study evaluated the interdependence of air temperature, radiant heat, wind velocity and noise intensity; it was revealed that less noise in forests positively affects other factors' intensity. Consequently, a forest setting is more comfortable for people than in an urban setting during the summers [43]. The psychological responses to physical environments are also significantly related to air temperature, relative humidity, radiant heat, and wind velocity.…”
Section: Resultsmentioning
confidence: 99%
“…Classroom noise is known to cause distraction and annoyance in children, but its primary effect is a reduction in speech intelligibility (for reviews, see Shield and Dockrell, 2003;Klatte et al, 2013), with a consequently negative impact on academic achievement (Shield and Dockrell, 2008). In typically developing children, the ability to cope with speech in noise (SiN) has been linked to individual differences in cognitive and language abilities (Nelson et al, 2005;Strait et al, 2012;MacCutcheon et al, 2019), age (Corbin et al, 2016), gender (Prodi et al, 2019), and supra-threshold auditory processing abilities (Lorenzi et al, 2000), as well as environmental factors, including reverberation and the spatial, spectral and temporal characteristics of the background noise (MacCutcheon et al, 2018(MacCutcheon et al, , 2019McCreery et al, 2019).…”
Section: Introductionmentioning
confidence: 99%